Design of Current Controller for Stand-Alone Type Solar Street Light using Low-Cost Device - Jeong, Da-Woom; Ahn, Young-Tae; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2026)
Background/Objectives: In recent years, the use of renewable energy tends to be drawing attention due to global warming and deterioration of environmental problems.Methods/Statistical analysis: Electrical grid construction utilizing sunlight, which is attracting attention as a next generation energy source among them, is being actively advanced, and this paper focused on the design of street lights using solar power generation.Findings: As a light source, energy saving and environmentally friendly LEDs were adopted. Due to the characteristics of the LED is sensitive to the current and temperature changes, so LED driving drivers for constant current control are required. Also, because the solar power generation time and the street lamp operation time are different, energy time shift is carried out through the battery, and because of the LED driving and battery charging needs constant current control, so constant current control design is indispensable.Improvements/Applications: In this paper, in order to reduce the price burden in the design of the controller, we designed the battery charge drive and the LED driver using the low-cost device. We also constructed a solar street light system based on the proposed method and verified its validity.
Keywords: Solar Power; Street Light; LED; Battery; Buck Converter